Recombinant viral vaccines expressing merozoite surface protein-1 induce antibody- and T cell-mediated multistage protection against malaria. - Draper, S; Goodman, A; Biswas, S; Forbes, E; Moore, A; Gilbert, S; Hill, A (2009)
Protecting against both liver and blood stages of infection is a long-sought goal of malaria vaccine design. Recently, we described the use of replication-defective viral vaccine vectors expressing the malaria antigen merozoite surface protein-1 (MSP-1) as an antimalarial vaccine strategy that elicits potent and protective antibody responses against blood-stage parasites. Here, we show that vaccine-induced MSP-1-specific CD4(+) T cells provide essential help for protective B cell responses, and CD8(+) T cells mediate significant antiparasitic activity against liver-stage parasites. Enhanced survival is subsequently seen in immunized mice following challenge with sporozoites, which mimics the natural route of infection more closely than when using infected red blood cells. This effect is evident both in the presence and absence of protective antibodies and is associated with decreased parasite burden in the liver followed by enhanced induction of the cytokine IFN-gamma in the serum. Multistage immunity against malaria can thus be achieved by using viral vectors recombinant for MSP-1.